STRATEGIES AND CHALLENGES OF ENGLISH EDUCATION STUDENTS IN VOCABULARY MASTERY - Laoli, Adieli; Giawa, Nurul Hikmah; Zebua, Dwi Putri Juwita; Namo, Elnardus Fransiskus Jafrinus (ELTIN Journal, 2025)
This study explores the perceptions and experiences of English education students regarding vocabulary mastery, with a focus on the strategies they employ, the challenges they encounter as well as how they overcome those challenges. Utilizing a qualitative descriptive design, the research captures detailed and nuanced insights into participants’ perceptions and experiences. Ten undergraduate students majoring in English Education were purposefully selected as participants to provide in-depth perspectives. Data were gathered through semi-structured interviews, which encouraged open discussions while addressing themes closely aligned with the research objectives. This study reveals that students face challenges in memorization, contextual usage, retention, and motivation. To overcome these challenges, they employ strategies such as repetition, using vocabulary in meaningful contexts, and incorporating multimedia resources. Additionally, students reported using fun and interactive methods, like songs and movies, to stay motivated and engaged. The findings highlight the importance of regular practice, contextual learning, and engaging methods to improve vocabulary mastery.